Association of physical activity, alcohol consumption and body mass index with the quality of life of adolescents - Alex Pinheiro Gordia (Universidade Federal de Santa Catarina, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n3p313 To investigate the relationship of Physical Activity Level (PAL), alcohol consumption and Body Mass Index (BMI) with the Quality of Life (QL) of adolescents. Methods: 608 adolescents, aged between 14 and 20 years participated in the study. All subjects were elementary students in the city of Lapa, Paraná State, Brazil. Body mass and stature were measured to calculate BMI. To measure socioeconomic status, QL, PAL and alcohol consumption the following instruments were used: a) ABEP questionnaire; b) WHOQOL-Bref; c) IPAQ; d) AUDIT. Statistical analysis employed Student's t test, one-way ANOVA, binary chi-square test and multinomial logistic regression. Results: Adolescents who were less active, probably dependent on alcohol, obese and female were the most vulnerable groups to having low QL. The majority of adolescents had high PAL (76,8%) or moderate PAL (20,9%) and only 2.3% had low PAL. Female adolescents and students who studied during the mornings constituted the group at risk of low PAL. The majority of students investigated presented reduced levels of alcohol consumption, however, 17.4% of adolescents presented at-risk alcohol consumption, 4.6% were high risk and 2.4% were probable alcohol dependents. The older male adolescents and evening students were the most vulnerable group for alcohol consumption. The prevalence rates of underweight, normal weight, overweight and obesity were 2.3%, 84.7%, 11.0% and 2.0%, respectively. Adolescents in socioeconomic class A were more vulnerable to obesity. Conclusion: The main subgroups of adolescents who exhibit risk of low QL were composed of less active individuals, probably dependent on alcohol, obese students and females. Based on these fi ndings, certain interventions for improving the living conditions of this population could be designed for implementation within the school environment, especially during Physical Education lessons.